Improving Process Capability of The Electronics Component Company Through SMED - Herlambang, Hendi (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2020)
Every industry wants to increase the speed of the production process to meet customer needs. This paper aims to show the results that have been achieved after the implementation of SMED in the stamping department of an electronic component company. Steps to Define, Measure, Improve, Control, and Improve are methods to achieve this research's objectives. The Work-Study method is used to perform activity decomposition to facilitate the repair process. Implementing SMED in electronics companies can reduce change over time by up to 41%.